Computational systems pharmacology analysis of Tong-Jing-Yi formula in the treatment of dysmenorrhea - Yueyan Li; Jialei Zhu; Jing Tang (IMR Press, 2022)
Background: Tong-Jing-Yi (TJY) formula consists of Leonurus, fried Toosendan and processed Cyperus, etc. The therapeutic effect of TJY on dysmenorrhea has been clinically validated, but the underlying mechanism remains unclear. The present study aimed to explore the possible molecular targets of TJY and the potential mechanisms. Methods: The components of TJY formula were identified by ultra performance liquid chromatography-quadrupole-time of flight/mass spectrometry. SwissTargetPrediction database was used to predict the targets of TJY formula, and targets associated with primary dysmenorrhea were also collected through other databases. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted. Results: A total of 91 compounds with identified structures were screened, including 3 groups of isomers. The results predicted 854 TJY formula-related targets and 363 disease-related targets. GO and KEGG analysis showed that the top 5 target genes were PIK3CA, AKT1, EGFR, AKT2 and CYP19A1. PI3K-Akt signaling, chemokine signaling, focal adhesion, and Rap1 signaling were ranked in the top 15 pathways. Conclusion: TJY formula might play roles in the treatment of dysmenorrhea underlying mechanisms relating to the involvement of TNF-α, interleukin and PI3K-Akt signaling pathway. Potential pathways have been identified that need mechanistic confirmation in a laboratory setting in the future.